Avaliação do uso de óxidos metálicos derivados de estruturas metal-orgânica (MOFs) como sensores eletroquímicos e eletrocatalisadores - Hortencio, Johnnys da Silva (2023)
In recent years, MOFs (Metal Organic Frameworks) have stood out due to their structural versatility and adjustable porosity, which has provided us with a promising perspective in various applications such as gas storage and separation, controlled drug rele ase, sensing and electrocatalysis. However, an improvement in the electrochemical properties of MOFs is still necessary to enhance their attributes to satisfy their applications as sensors and electrocatalysts for fuel cells and water electrolysis. Electro catalytic water splitting has received widespread attention due to the slow kinetics of the reaction and the complex electron transfer process, the oxygen evolution reaction (OER) occurring at the anode has become a major obstacle. The improved OER perform ance is attributed to the significant enhancement in accessible surface active sites and the decrease in charge transfer resistance. The exploration of efficient, cheap and stable electrocatalysts for OER is of great importance for energy conversion and st orage. Currently, transition metal oxides (TMOs) have enormous potential as electrode materials due to their low cost, redox chemistry and high chemical stability. In this work, an impregnation method is demonstrated to synthesize Cu based metal oxides dop ed with Mn and Ni as high efficiency, low energy electrocatalytic materials for the oxygen evolution reaction under alkaline conditions. For the synthesis of these materials, copper (II), manganese (II) and nickel (II) salts were used, deionized water as s olvent and iminodiacetic acid as ligand, called [Cu(IDA)(H 2 O) 2 n ,(IDA=iminodiacetate),[Cu 0.9 Mn 0.1 (IDA)(H 2 O) 2 n ,[Cu 0.7 Mn 0.3 (IDA)(H 2 O) 2 n ,[Cu 0 .5 Mn 0.5 (IDA)(H 2 O) 2 n ,[Cu 0.9 Ni 0.1 (IDA)(H 2 O) 2 n ,[Cu 0.7 Ni 0.3 (IDA)(H 2 O) 2 n and [Cu 0.5 Ni 0.5 (IDA)(H 2 O) 2 n . For the synthesis of metal oxides, the aforementioned MOFs were calcined under an atmosphere of atmospheric air, leading to the formation of the electrocatalysts CuO, CuO/Cu 2 O/Mn x and Cu 1 x Ni x O (x=10, 30 and 50% n/n), respectively. The materials were calcined in their structural, morphological and compositional aspects. Copper oxide based materials were applied as an electrochemical sensor and as electrocatalysts for OER in alkaline media at a current density of 10 mA cm 2 . Electrochemical tests using carbon paste electrodes modified with CuO and CuO/Cu 2 O/Mn50 were carried out to evaluate the voltammetric behavior of the redox probe [Fe( 6 3 --/4 (0.05M) in KCl electrolyte solution 0.1 mol L 1 using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), where the anodic and cathodic peaks presented a definition. All materials showed good overpotential values of 359, 355, 355, 360, 352, 346 and 340 mV at a current density of 1 0 mA cm 2 . The Tafel slopes are 83.8, 75.4, 75.1, 90.6, 82.5, 47, 65, and 54 mV dec 1 , respectively, with very small attenuation for long term catalytic reaction. Furthermore, the electrocatalysts showed short term electrochemical stability for 12h. Theref ore, the present method opens a new avenue for the preparation of efficient and low cost materials for OER application. Electroanalysis of dopamine (DA) in EPC modified with CuO and CuO/Cu application. Electroanalysis of dopamine (DA) in EPC modified with CuO and CuO/Cu22O/Mn50 O/Mn50 showed that dopamine detection can best be achieved at around 0.35 V. The detection limit for the showed that dopamine detection can best be achieved at around 0.35 V. The detection limit for the EPC/CuO sensor determined via voltage voltammetry differential pulse (DPV) was 1.45 µM over a EPC/CuO sensor determined via voltage voltammetry differential pulse (DPV) was 1.45 μM over a wide linear range of 0.02 wide linear range of 0.02 –– 25 µM, in which it showed goo25 μM, in which it showed good reproducibility, although it had relatively d reproducibility, although it had relatively low stability.low stability.